2011
DOI: 10.1186/1471-2202-12-53
|View full text |Cite
|
Sign up to set email alerts
|

Primary Neuronal Precursors in Adult Crayfish Brain: Replenishment from a Non-neuronal Source

Abstract: BackgroundAdult neurogenesis, the production and integration of new neurons into circuits in the brains of adult animals, is a common feature of a variety of organisms, ranging from insects and crustaceans to birds and mammals. In the mammalian brain the 1st-generation neuronal precursors, the astrocytic stem cells, reside in neurogenic niches and are reported to undergo self-renewing divisions, thereby providing a source of new neurons throughout an animal's life. In contrast, our work shows that the 1st-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(152 citation statements)
references
References 52 publications
8
142
2
Order By: Relevance
“…The first-generation precursors in the crayfish P. clarkii undergo geometrically symmetrical divisions and both daughter cells migrate away [32], suggesting that these divisions are not self-renewing. This has been confirmed in experiments that directly tested the self-renewal capacity of the niche cell population [30]. Hence, the first-generation neuronal precursors are not typical neuronal stem cells.…”
Section: Discussionmentioning
confidence: 74%
“…The first-generation precursors in the crayfish P. clarkii undergo geometrically symmetrical divisions and both daughter cells migrate away [32], suggesting that these divisions are not self-renewing. This has been confirmed in experiments that directly tested the self-renewal capacity of the niche cell population [30]. Hence, the first-generation neuronal precursors are not typical neuronal stem cells.…”
Section: Discussionmentioning
confidence: 74%
“…Earlier, this tissue was thought to be restricted to the dorsal part of the stomach. However, since previous reports have indicated that neuronal stem cells in the crayfish brain are derived from an external source [13,14] and because several genes that we have isolated from crayfish are limited in expression to the HPT and cells in nerve and brain tissues [9,12], we asked whether there is a physical link between the HPT and the brain. By a careful dissection of this thin and fragile tissue, we can now demonstrate that the HPT extends forward and connects to the brain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that hemocyte number and the plasma level of Color images available online at www.liebertpub .com/scd the hematopoietic cytokine, Ast1, oscillates in a typical circadian rhythmic manner in crayfish [18]. Moreover, a study conducted on adult Procambarus clarkia crayfish suggested that HPT cells possibly serve as a primary source of neuronal precursor cells [13]. In mammals, a brain-bone-blood link has been proposed to require signals delivered from the central nervous system directly to the hematopoietic stem and progenitor cells or indirectly to the niche that controls HSC proliferation, mobilization, and differentiation [22].…”
Section: Discussionmentioning
confidence: 96%
“…Song et al (2009) were also unable to demonstrate a connection between the vascular system and the niche in P. clarkii . However, injection of a low molecular weight fluorescent dye into the perfused brain via the dorsal artery (Figure 4D) or directly into the pericardium of P. clarkii resulted in the clear presence of this dye within the cavity (Sullivan et al, 2007a; Benton et al, 2010), as did injections into the dorsal artery of Cherax destructor (Sandeman et al, 2009). Dye injection into the cavity itself also suggests some form of physical connection, as dye fills not only the cavity, but also nearby vessels (Sandeman and Beltz, unpublished results).…”
Section: The Deutocerebral Organmentioning
confidence: 99%
“…These precursors undergo symmetrical divisions, unlike traditional neuroblasts, and their divisions are not self-renewing (Zhang et al, 2009; Benton et al, 2010). The cells are bipolar, a structural feature that is clearly distinct from neuroblasts found in the embryonic brain; it has been proposed that the processes of the bipolar cells guide the migration of the 2nd generation cells in the neural precursor lineage to sites of further proliferation and differentiation, proliferation zones in CL9 and CL10.…”
Section: Introductionmentioning
confidence: 99%